2015
DOI: 10.1371/journal.pone.0128815
|View full text |Cite
|
Sign up to set email alerts
|

Virus Excretion from Foot-And-Mouth Disease Virus Carrier Cattle and Their Potential Role in Causing New Outbreaks

Abstract: The role of foot-and-mouth disease virus (FMDV) carrier cattle in causing new outbreaks is still a matter of debate and it is important to find out these carrier animals by post-outbreak serosurveillance to declare freedom from FMDV infection. In this study we explore the differences in viral shedding between carrier and non-carrier animals, quantify the transmission rate of FMDV infection from carriers to susceptible animals and identify potential viral determinants of viral persistence. We collected nasal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 36 publications
(55 reference statements)
6
76
0
Order By: Relevance
“…The evolutionary rate estimated in this study was similar to the rate reported for other serotype O carrier viruses (2.6 × 10 -2 s/s/y;(25)).In contrast, the rate reported in this study was an order of magnitude faster than the rate reported for O/ME-SA/Ind2001 outbreak isolates collected in India between 2000 – 2013 (6.338 × 10 -3 s/s/y;(41)). Similarly, previous studies have shown the rate of evolution of serotype C carrier viruses was an order of magnitude faster than the rate reported for serotype C outbreak viruses collected over a period of six decades (59, 64).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The evolutionary rate estimated in this study was similar to the rate reported for other serotype O carrier viruses (2.6 × 10 -2 s/s/y;(25)).In contrast, the rate reported in this study was an order of magnitude faster than the rate reported for O/ME-SA/Ind2001 outbreak isolates collected in India between 2000 – 2013 (6.338 × 10 -3 s/s/y;(41)). Similarly, previous studies have shown the rate of evolution of serotype C carrier viruses was an order of magnitude faster than the rate reported for serotype C outbreak viruses collected over a period of six decades (59, 64).…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have reported the antigenic and genetic variants of FMDV in the virus population recovered from persistently infected cattle and buffalo under experimental conditions (12, 25, 28-32) or under natural field conditions (14, 17, 21, 33-37). Although within-host genetic variation is common during persistent infection, no consistent genetic changes associated with persistent infection have been identified across studies.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a variable proportion of animals in a herd may be subclinically infected and do not show any clinical signs of infection. This phenomenon is most common amongst vaccinated animals (McVicar & Sutmoller, ; Parthiban, Mahapatra, Gubbins, & Parida, ; Stenfeldt, Eschbaumer et al., ). In some clinically and subclinically infected ruminants, FMDV can be isolated from oropharyngeal fluids and/or tissues >28 days after infection.…”
Section: Introductionmentioning
confidence: 99%
“…Such persistently infected animals from which virus can be isolated at least 28 days post‐infection are defined as “FMDV carriers.” The duration of this carrier state may vary from months to years (Hayer et al., ; Tenzin, Dekker, Vernooij, Bouma, & Stegeman, ). Although transmission from persistently infected cattle has not been proven under experimental conditions (Ilott, Salt, Gaskell, & Kitching, ; Parthiban, Mahapatra, Gubbins, & Parida, ), the presence of FMDV carriers in a population can severely impact foreign trade of all animal products (Kitching et al., ). In addition, the dynamics of the FMDV carrier state is relatively understudied in field conditions (Barend et al., ; Hayer et al., ).…”
Section: Introductionmentioning
confidence: 99%